PENGARUH GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPARATE SOCIAL RESPONSIBILITY TERHADAP KUALITAS LABA DAN DAMPAKNYA PADA RETURN SAHAM DENGAN LEVERAGE DAN FIRM SIZE SEBAGAI CONTROL VARIABLE - Diah Permata Sari; Wahyu Widodo (Jurnal Bina Bangsa Ekonomika, 2022)
The profit information disclosed by the company does not guarantee that the profit is of high quality. Profit can be said to be quality if the reported profit can be used by users of financial statements to make the best decisions and meet the qualitative characteristics of relevant and reliable financial statements and can convey the facts of actual financial performance. The objective to be achieved in this study is to test how the effect of the GCG Mechanism, CSR disclosure, on the quality of profits and its impact on the company's stock returns, with the control variables being Leverage and Firm Size. The population in this study is mining sector companies listed on the Indonesia Stock Exchange. The research data was taken from the Indonesia Stock Exchange website for the 2014-2018 period.  The method used is the Purposive Sampling method. The results of this study show that Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, and CSR Disclosure do not have a significant effect on the quality of profits, while the Audit Committee and Stock Returns have a significant effect on Profit Quality